An Established Early Rehabilitation Therapy Demonstrating Higher Efficacy and Safety for Care of Intensive Care Unit Patients - Pang, Yatao (Med Sci Monit, 2019)
BACKGROUND: Although survival rates of critically ill patients in Intensive Care Units (ICUs) have improved in recent years, many risk factors cause a few serious complications. This study aimed to evaluate efficacy and safety of comprehensive early rehabilitation therapy for ICU patients. MATERIAL/METHODS: This study recruited ICU patients who were diagnosed as having cerebral hemorrhage or traumatic brain injury. ICU patients were randomly divided into an early rehabilitation therapy group (Observation group, n=21) and a Control group (n=21). Patients in the Control group underwent persistent monitoring of respiratory functions and blood oxygen saturation, as well as electrocardiographic monitoring. ICU patients in the Observation group underwent individualized treatments based on conventional treatments. APACHE II scores, MRC scores, and consciousness improvement rates of ICU patients were evaluated. Incidences of adverse events and complications were also assessed. RESULTS: Early rehabilitation therapy significantly decreased APACHE II scores and significantly increased MRC scores compared to the Control group (p<0.05). Early rehabilitation therapy significantly improved consciousness of ICU patients compared to the Control group (p<0.05). Early rehabilitation therapy significantly reduced the incidence of complications compared to the Control group (p<0.05). Early rehabilitation therapy significantly shortened ICU or total hospital stay and mechanical ventilation time compared to the Control group (p<0.05). CONCLUSIONS: Early rehabilitation therapy decreased APACHE II scores, enhanced MRC scores, and improved consciousness of ICU patients. Moreover, early rehabilitation therapy also reduced the incidence of complications and shortened ICU or total hospital stay and mechanical ventilation time of ICU patients. Therefore, early rehabilitation therapy was shown to be effective and safe for ICU patients.